1995
DOI: 10.1046/j.1365-313x.1995.7020321.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a cloned plant K+ channel in Xenopus oocytes: analysis of macroscopic currents

Abstract: SummaryThe open reading frame from the Arabidopsis thaliana KAT1 cDNA was cloned in a transcription plasmid between the 3' and 5' untranslated regions of a J3-globin cDNA from Xanopus oocyte. The polyedenylated transcripts resulting from in vitro transcription gave rise to high levels of expression of KAT1 channel when injected in Xanopus oocytes. Upon hyperpolarization, a slow activating current could be recorded, inwardly-or outwardly-directed, depending on K + external concentration. Predictions of the volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
125
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(143 citation statements)
references
References 39 publications
18
125
0
Order By: Relevance
“…Furthermore, the shift of the activation potential in insect cells is accompanied by a shift of the deactivation kinetics towards more positive potentials. This results in a slower deactivation at more hyperpolarized potentials in Sf9 cells than in oocytes [12,25,26]. Similar observations were also made for animal ion channels, e.g.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…Furthermore, the shift of the activation potential in insect cells is accompanied by a shift of the deactivation kinetics towards more positive potentials. This results in a slower deactivation at more hyperpolarized potentials in Sf9 cells than in oocytes [12,25,26]. Similar observations were also made for animal ion channels, e.g.…”
Section: Resultssupporting
confidence: 74%
“…As in other expression systems in Sf9 cells, KAT1 channels are characterized by high K + selectivity, strong rectification as well as slow hyperpolarizationdependent activation. The voltage-dependent properties of KAT1 expressed in oocytes [12,14,21,25,26] are similar to inward-rectifying K+ channels in vivo [10]. The major difference of the in vitro studies of Schachtman et al [21] and Hedrich et al [12] to those reported here for Sf9 cells concerns the relative permeability of KAT1 for NH~ over K +.…”
Section: Resultssupporting
confidence: 48%
See 2 more Smart Citations
“…Whereas the Rb+ and NH,' conductances of KATl expressed in oocytes are approximately 20 to 30% of the K+ conductance (Schachtman et al, 1992), the mutations T256D and T256G evoked Rb+ and NH,' conductances that were 10 times larger than the K+ conductance (Uozumi et al, 1995). However, this large inversion in selectivity, as measured by conductance ratios, did not apply to the selectivity as measured by reversal voltage analysis (Uozumi et al, 1995), emphasizing the fact that the two different types of analysis are not comparable (Hille, 1992;Very et al, 1995).…”
Section: Cation Selectivity Of Plant K+ Channelsmentioning
confidence: 99%